PERLUNYA DESAIN COST SISTEM DALAM RANGKA MENGUBAH POSISI DAYA SAING BAGI PERUSAHAAN DI INDONESIA - Purwanto (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2015)
Based on the Global Competitive Report of 2014 - 2015, ranking the competitiveness of Indonesia to review the Year 2014 - 2015 from 144 countries in the World, Indonesia ranks to 34; among Asean Countries and still under country of Singapore, Malaysia, Brunei Darussalam and Thailand. One cause is the selling price less competitive, against the background cost of goods sold improper, mainly include overhead still using the calculation system / the traditional method; which will impact the determination of the cost per unit distortion product so unreliable measure efficiency and productivity. Determining the cost per unit more accurate as essentials management to review the basic fundamentals of decision making, for example, adopting with ABC formula. Efforts reaching competitive excellence, as well as eliminating non-value added activities, it’s time for a company in Indonesia to re-design of cost system.